Furthering sustainable development: The implementation of Green Procurement in Central and Eastern Europe Methods and Experiences from Hungarian Public and Private Organizations - Diófási-Kovács, Orsolya; Valkó, László (Problemy Ekorozwoju, 2015)
The aim of the article is to show how one of the most active and demonstrative management tool for furthering sustainable development can be successfully implemented through a Central and Eastern European example. The Green Procurement Hungary Project (GPH project) was conducted in order to develop a toolkit most suitable for implementing green (public) procurement, in order to use the enormous purchasing power of public and private organizations for furthering sustainable consumption, eco-production and all together sustainable development. The article shows the relationship between sustainable-, green- and social procurement, introduces the state-of-the art of green public procurement in the EU with specific attention to the CEE countries and shows the methodology developed in the GPH project. This methodology has great significance for practitioners and policy makers as well for the implementation of sustainable procurement. Even on the European level, for example by the development of funding opportunities and by the evaluation of project proposals these experiences are valuable.